1995
DOI: 10.1177/002199839502901606
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of T-Shaped Structural Composite through Resin Transfer Molding

Abstract: Resin transfer molding (RTM) combines resin impregnation and composite fabrication in one process. It simplifies the process for composite fabrication and has the advantages of automation, low cost, and versatile design of fiber reinforcements. The RTM process was used in this study to fabricate T-shaped stuctural composites. Edge effects due to the gap between the fiber mats and the mold or the imperfect sealing of the matting mold resulted in edge channeling flows, leading to dry spot enclosure in the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The material and process parameters in LCM manufacturing exhibit variations (21,22). Most commonly, the preform permeability can vary along the edges due to imperfect fit and non-repeatable placement.…”
Section: Sensing and Controlmentioning
confidence: 99%
“…The material and process parameters in LCM manufacturing exhibit variations (21,22). Most commonly, the preform permeability can vary along the edges due to imperfect fit and non-repeatable placement.…”
Section: Sensing and Controlmentioning
confidence: 99%
“…Young and Chuang [8] investigated T-joints fabricated using resin transfer molding and transverse stitching of the flange at an offset distance form the web-to-flange interface. T-joint ultimate failure under tension loading was shown to be improved using transverse stitching.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element analysis (FEA) was performed to predict pull-off strength and fracture mechanics was used to predict delimitation failure. T-joints with transverse stitching using the RTM process and Ciba-Geigy epoxy resin were evaluated by Young et al [7]. They showed that transverse stitching along the rib at an offset distance from the web improved the pull-off strength of T-joints.…”
Section: Introductionmentioning
confidence: 99%